(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
The proper design of enclosures for wild animals is essential to promote the expression of their behavioral needs, providing opportunities for choice and control over their environment, thereby enhancing their quality of life. This study aimed to assess and propose improvements to the enclosure design of a Leopardus geoffroyi specimen in captivity to promote its welfare. Direct observations were conducted using ad libitum sampling to create the ethogram and focal sampling to obtain the behavioral budget. Additionally, space use was analyzed with the modified Spread of Participation Index, and enclosure quality was assessed using the environmental indicators of the Ackonc-AWA protocol. The results showed low levels of locomotion and exploration, with a preference for the upper part of the enclosure, suggesting structural limitations. The environmental evaluation revealed major deficiencies in 79% of the indicators and minor deficiencies in 14%. The combined use of these methodologies allowed us to identify key problems and propose an enclosure design, both external (exhibition) and internal (management), adapted to the needs of the animal. It is recommended to continue assessing the impact of these changes to ensure improvements in welfare. This methodology could be applied to other species under human care.